2017
DOI: 10.1007/s10493-017-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of oribatid mite species diversity: testing the effects of elevation, area and sampling effort

Abstract: Elevational gradients in species diversity and species area relationships are two well established patterns that are not mutually exclusive in space and time. Elevation and area are both considered as good proxies to detect and characterize the patterns of species diversity distribution. However, such studies are hampered by the incomplete biodiversity data available for ecologists, which may affect the pattern perceptions. Using the large dataset of oribatid mite communities sampled in Georgia, we tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In our study, spatial filtering strongly correlated with the soil surface‐dwelling Oribatida community, consistent with our third Hypothesis. The elevation is a vital compound variable in montane ecosystems (Mumladze et al, 2017). We found that the elevation had an extremely significant effect on the community structure of soil surface‐dwelling Oribatida.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, spatial filtering strongly correlated with the soil surface‐dwelling Oribatida community, consistent with our third Hypothesis. The elevation is a vital compound variable in montane ecosystems (Mumladze et al, 2017). We found that the elevation had an extremely significant effect on the community structure of soil surface‐dwelling Oribatida.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent patterns of Oribatida along an altitudinal gradient are subject to environmental factors, geographical distance, and specific species characteristics (Illig et al, 2010; Marian et al, 2018). Influenced by these factors, the altitudinal diversity patterns of Oribatida generally decline linearly (Mumladze et al, 2017) or peak at an intermediate altitude, where the primary productivity is the highest (Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%